Kinetics and mechanism of the nickel electrode : I. Acid solutions containing a high concentration of chloride and nickel ions - Vilche, Jorge Roberto (1975)
The kinetics of the Ni electrode in acid solutions with a high chloride ion concentration has been investigated in the range of 25–75°C. Dissolution occurs uniformly only at low anodic potentials. When the latter exceeds a critical value, Ecrit, net localized metal corrosion takes place. The <mtext>E</mtext><mtext>ln</mtext><mtext> i</mtext>a plot at E < Ecrit corresponds to a curve approaching two limiting slopes, namely, <mtext>2RT</mtext><mtext>3F</mtext> at (<mtext>E − E</mtext><mtext>rest</mtext><mtext>) → 0, </mtext><mtext>and</mtext><mtext> </mtext><mtext>2RT</mtext><mtext>F</mtext><mtext> </mtext><mtext>at</mtext><mtext> E → E</mtext><mtext>crit</mtext>. The cathodic Tafel slope is <mtext>2RT</mtext><mtext>F</mtext>. These results, including their pH dependence, are explained with a reaction mechanism involving the participation of adsorbed hydroxo-species.